2002
DOI: 10.1038/sj.jhh.1001372
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angiotensin II on pulse wave velocity in humans is mediated through angiotensin II type 1 (AT1) receptors

Abstract: The objective of this study was to examine the effect of angiotensin II (Ang II) and angiotensin II type 1 (AT 1 ) receptor blockade on pulse wave velocity (PWV) in healthy humans. We studied nine young male volunteers in a double-blind randomised crossover design. Carotidfemoral PWV (an index of arterial stiffness) was measured by using a Complior  machine. Subjects were previously treated for 3 days with once-daily dose of either a placebo or valsartan 80 mg. On the third day, they were infused with either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…50 Clinical and experimental studies suggest that the reninangiotensin system may act on the geometry and stiffness of the large artery wall. 44 In a recent review of factors influencing arterial stiffness, Safar and Benetos 44 suggested that the effects of the renin-angiotensin system may clarify several aspects of the pathophysiology of hypertension in the elderly.…”
Section: Renin-angiotensin System and Arterial Stiffnessmentioning
confidence: 99%
See 3 more Smart Citations
“…50 Clinical and experimental studies suggest that the reninangiotensin system may act on the geometry and stiffness of the large artery wall. 44 In a recent review of factors influencing arterial stiffness, Safar and Benetos 44 suggested that the effects of the renin-angiotensin system may clarify several aspects of the pathophysiology of hypertension in the elderly.…”
Section: Renin-angiotensin System and Arterial Stiffnessmentioning
confidence: 99%
“…The authors concluded that the advantageous haemodynamic effects of the ACE inhibitor/diuretic combination reflect changes of wave reflections issued from distal arterial and arteriolar territory, where the ACE inhibitors are known to improve vessel wall structure. 67 Further to the important local actions of angiotensin II on arterial stiffness via the AT 1 receptor, 50 there are additional reasons to believe that blocking of the renin-angiotensin system using angiotensin AT 1 receptor blockers (ARBs) can regulate vascular function. The ARB irbesartan has been shown to exert anti-inflammatory properties in patients with early 68 or advanced atherosclerosis, 69 whereas candesartan has also been shown to reduce inflammatory cytokines and to reverse endothelial dysfunction.…”
Section: Effects Of Antihypertensive Drugs On Arterial Stiffnessmentioning
confidence: 99%
See 2 more Smart Citations
“…12 These findings in relation to the thiazide diuretics and the angiotensin II blockers are novel. [13][14][15] Thiazide diuretics have different pharmacologic properties that may affect arterial aging. Indeed, the increase in arterial stiffness with thiazide use might be linked by the calcium metabolism.…”
mentioning
confidence: 99%